2020
DOI: 10.1182/blood.2019003127
|View full text |Cite
|
Sign up to set email alerts
|

Brentuximab vedotin with chemotherapy for stage III/IV classical Hodgkin lymphoma: 3-year update of the ECHELON-1 study

Abstract: The phase 3 ECHELON-1 study demonstrated that brentuximab vedotin (A) with doxorubicin, vinblastine, and dacarbazine (AVD; A+AVD) exhibited superior modified progression-free survival (PFS) vs doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) for frontline treatment of patients with stage III/IV classical Hodgkin lymphoma (cHL). Maturing positron emission tomography (PET)-adapted trial data highlight potential limitations of PET-adapted approaches, including toxicities with dose intensification and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 16 publications
3
59
0
5
Order By: Relevance
“…Since the primary analysis, this patient population has also been assessed at a median follow‐up of approximately 3 years. A previously published analysis of the ITT population at 3 years demonstrated the durable benefit of A + AVD versus ABVD in patients independent of age, disease stage, or risk‐factor score without requiring change of therapy or exposure to bleomycin 13 . In this analysis of patients with Stage IV disease, an analysis of PFS by investigator demonstrated an improvement that was maintained at 3 years with A + AVD versus ABVD, with a reduction in the risk of a PFS event of 28% (HR, 0.723; 95% CI, 0.537–0.973).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since the primary analysis, this patient population has also been assessed at a median follow‐up of approximately 3 years. A previously published analysis of the ITT population at 3 years demonstrated the durable benefit of A + AVD versus ABVD in patients independent of age, disease stage, or risk‐factor score without requiring change of therapy or exposure to bleomycin 13 . In this analysis of patients with Stage IV disease, an analysis of PFS by investigator demonstrated an improvement that was maintained at 3 years with A + AVD versus ABVD, with a reduction in the risk of a PFS event of 28% (HR, 0.723; 95% CI, 0.537–0.973).…”
Section: Discussionmentioning
confidence: 96%
“…Full details of the ECHELON‐1 study (http://ClinicalTrials.gov identifier NCT01712490; EudraCT 2011‐005450‐60) have been published 12,13 . Briefly, we recruited patients aged ≥18 years with histologically confirmed cHL (Ann Arbor stage III or IV) who had not been previously treated with systemic chemotherapy or radiotherapy and had an Eastern Cooperative Oncology Group performance status of 0–2 (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…BV regimen 36. Prolonged follow-up results published in March 2020 confirmed the durability of response observed with AVD + BV 37. A subsequent double-blind, randomized phase III trial ECHELON-2 [ClinicalTrials.…”
mentioning
confidence: 90%
“… 36 Prolonged follow-up results published in March 2020 confirmed the durability of response observed with AVD + BV. 37 A subsequent double-blind, randomized phase III trial ECHELON-2 [ClinicalTrials.gov identifier: NCT01777152] compared BV in combination with cyclophosphamide, doxorubicin and prednisone (BV + CHP) to cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) in 452 patients with previously untreated CD30 + PTCL. Patients were treated with BV + CHP or CHOP for six to eight 21-day cycles.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with advanced stage disease, six cycles of ABVD with an interim PET 2 evaluation remains an option (44) and bleomycin is to be omitted in the following cycles after a negative PET 2, based on the results of RATHL study (risk-adapted therapy for HL) which showed no difference in 3 years progression-free survival (PFS) between 2 cycles of ABVD (45), followed by 4 cycles of AVD and 6 cycles of ABVD. It is also possible to consider A+AVD (brentuximab bedotin, doxorubicin, vinblastine, dacarbazine) regimen omitting bleomycin and introducing adcetris (anti CD30-brentuximab vedotin) based on the results of ECHELON-1 study which demonstrated that brentuximab vedotin (A) with AVD exhibited superior modified PFS vs. ABVD for frontline treatment for patients with stage III/IV classical HL (46), and because of the approval in Lebanon of A + AVD for first line therapy for…”
Section: First Line Therapymentioning
confidence: 99%